1998
DOI: 10.1002/ctpp.19980380126
|View full text |Cite
|
Sign up to set email alerts
|

Density, Temperature and Potential Fluctuation Measurements With Multiple Fast Swept Langmuir Probes on W7-AS

Abstract: To measure fluctuations of plasma density, electron temperature and electric plasma potential in the edge of fusion experiments simultaneously and with high spatial resolution, the best approach is generally agreed to be the fast sweeping of the Langmuir probe characteristic, a technique which has been applied on several experiments in the past few years. "Fast" in this context means that the sweep frequency should be well above typical fluctuation frequencies which are known to range up to a few 100 kHz. A ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Usually a factor about 3 is used for α which was also experimentally found at ASDEX Upgrade [10]. Nevertheless strong deviations from this factor are possible [11]. For a typical probe tip distance of a few mm a T e variation of 1 eV between the pins already causes ΔE ∼ 200 − 300 V/m.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Usually a factor about 3 is used for α which was also experimentally found at ASDEX Upgrade [10]. Nevertheless strong deviations from this factor are possible [11]. For a typical probe tip distance of a few mm a T e variation of 1 eV between the pins already causes ΔE ∼ 200 − 300 V/m.…”
Section: Introductionmentioning
confidence: 97%
“…In fusion devices swept single probes are usually used at rather low sweeping frequencies (kHz range). About a decade ago theoretical and experimental investigations on fast swept single probes were made up to the MHz range [11,[21][22][23] showing at high frequencies a hysteresis in the electron saturation branch. This is caused by a polarization current due to the potential difference of the flux tube intersected by the probe and the surrounding plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Blobs detach from the main plasma and move radially outwards, making turbulence at the edge of fusion devices intermittent and significantly contributing to the radial transport mechanisms in the SOL. Blobs have been observed in tokamaks (e.g., in the Caltech Research Tokamak, 2 Alcator C-Mod, 3 JET, 4 JT-60U, 5 Tore Supra, 6 and TCV 7 ), stellarators (e.g., in the W7-AS stellarator 8 and in TJ-K 9 ) reversed field pinches, 10 and basic plasma devices (e.g., in LAPD 11 and in TORPEX 12 ). They can lead to enhanced intermittent heat flux on the main vessel wall, possibly damaging radio frequency antennas and wall tiles and causing sputtering of impurities.…”
Section: Introductionmentioning
confidence: 99%
“…And the electron energy distrubution function (EEDF) is not represented by the second derivative of the V-I characteristic (Druyvesteyn formula [11]) but rather by its first derivative [12,13]. Meamwhile, some experiments were targeted on this issue with the comparison to other diagnostics, such as emissive probe, et al [18][19][20][21][22][23][24][25][26]. Most of them showed that many statistical properties of fluctuations inferred by Langmuir probes and other diagnostics, such as standard deviation, auto and cross correlation, auto and cross power, cross phase and cross coherency spectra, were similar.…”
Section: Nuclear Fusionmentioning
confidence: 99%